Eyetracking in der Kommunikations- und Medienwissenschaft: Theorie, Methode und kritische Reflexion - Stephanie Geise (Studies in Communication, Media, 2011)
Although eye tracking does not yet represent a standard instrument of communication and media science, it has been used more and more frequently in the last years as single method or in method combination. The fascination of the reconstruction of the human gaze is „eye catching“: as an apparative, physiological, reception-accompanying observation method eye tracking captures the majority of the genuine eye movement and allows a description and analysis qualitatively as well as quantitatively. In this way, eye tracking provides a fairly accurate reference point, with regards to what content is foveally fixated by recipients during the visual perception process of the visual stimulus, with what intensity recipients visually turn towards the content or information, in what temporal and contextual order the observation happens and where no visual attention is attributed. In contrast, eye tracking alone provides no or only little potential for answering questions such as what content recipients perceive of the visual stimulus in the peripheral or para-foveal perception space, why or with what intention or motivation they turn towards the stimulus, what the recipients think or feel while observing the visual stimulus or what subsequent emotional or cognitive processes are attached to the perception of the respective visual detail.